Effect of Pterygium Size on Astgmatism and Corneal Topography Before and After Surgery - Mochammad Sjarifudhin; Gatut Suhendro (Majalah Oftalmologi Indonesia, 2015)
Background: Objective: To analyze the association between pterygium size with astigmatism and corneal topography changes before and after surgery. Methods: This study was conducted at Dr. Soetomo General Hospital and Surabaya Eye Clinic on February-June 2013. In 31 eyes of 20 patients with primary pterygium, size of pterygium was measured in millimeters from the limbus (horizontal length) by caliper and the beam of slit lamp microscope. Twenty four eyes with pterygium type 2 and 3 were excised with bare sclera technique and intraoperative MMC application. Astigmat and corneal topography was investigated with the help of Orbscan preoperatively and 4-6 weeks postoperatively. Result: The size of pterygia had a significant correlation on the elevation of the preoperative corneal astigmatism and irregularities (p<0.001). The mean Sim K astigmatism (p=0.005) and irregularity index (<0.001) significantly decreased after pterygium surgery. The mean refractive power significantly increased after the operation (p<0.001). Conclusion: Pterygium leads to significant changes in corneal refractive status, which increase with the increase in the size of pterygia and improve following pterygium surgery. Keywords: Pterygium, astigmatism, corneal topography